(untitled) (Forum for Linguistic Studies, 2024)
Barbara Kingsolver, the 2010 Orange Prize-winning author, has always been deeply aware of nature and the environment. Climate change, as a global phenomenon, often lies at the heart of her fiction. Barbara Kingsolver’s novel Flight Behaviour is a moving examination of human agency, ecological crisis, and the intricate relationships between nature, community, and hope. The novel, which is set in rural Tennessee, tackles pressing environmental issues while providing a story of resiliency and change. Kingsolver skilfully interweaves themes of environmental consciousness and the possibility of hope amid ecological upheaval through an engaging narrative. This research paper is an attempt to analyse Flight Behaviour, by Barbara Kingsolver, which falls under the genre of climate fiction. The novelist tries to present an amalgamation of the unreal and the real world climate change impasse, reality and imagination to impose a detailed account of eco catastrophes. The term "alarmism" is frequently used to describe climate change. Kingsolver’s Flight Behaviour captures the truth of this "alarmism" and the truth of monarch butterfly migration. It resonates with topics like climate change, man-made disasters, environmental preservation, and environmental consciousness, among others. This paper specifically examines the protagonist Dellarobia’s journey towards environmental consciousness from an ecological perspective. It depicts her journey as she changes from an anthropocentric, lifeless housewife to an environmentally conscious, responsible custodian of the world around her. The transitions represent her ignorance of the reality and worthiness of Monarch Butterflies, the gruesome face of climate change and the impending catastrophe, the challenges and obstacles she faces in convincing her town’s residents to acknowledge the truth about climate change on individual, environmental, economic, and political grounds, and finally the lessons she learns from nature. The survival and flight of the butterflies itself stands a life lesson from nature that the protagonist takes forward.